Avaliação imuno-histoquímica da BMP-2, BMP-4 e seus receptores (BMPRIA e BMPRII) em ameloblastomas e tumor odontogênico adenomatóide - Nascimento, Marcelo Anderson Barbosa (2014)
BMPs are components superfamily ligands transformation growth fator-β (TGF-β) secreted into the extracellular environment, with mechanisms of intercellular communication through specific ligands and receptors in various target cells, being recognized for its influence in osteogenic induction, also play an important role in tissue homeostasis, cell proliferation, differentiation control , in addition to being present in the development of various malignancies. The aim of this study was to compare the immunohistochemical expression of BMP-2, BMP-4 and its receptors BMPRIA and BMPRII in cases of ameloblastoma and adenomatoid odontogenic tumor. The sample consisted of 20 cases of solid ameloblastoma (SA), 10 cases of ameloblastoma unicystic (UA) and 16 cases of adenomatoid odontogenic tumor (AOT). The expression of BMPs and their receptors was evaluated in the parenchyma and stroma of lesions, establishing the percentage of immunopositive cells (0 - negative; 1-1 % to 10 % of cells positive; 2 - 11% to 25% of positive cells; 3 - 26% to 50% of cells positive; 4 - 51% to 75 % of positive cells; 5 - more than 75% positive cells). Analysis of the expression of BMP-2 revealed no statistically significant differences in parenchymal (p = 0.925) and stromal component (p = 0.345) between the groups, as well as BMP-4 (p = 0.873 / p = 0.131). In the epithelial component, SA and AOT had a higher frequency of score 5. In turn, all cases of UA were classified as score 5. The analysis of the stromal component showed no statistically significant difference between groups with respect to median scores BMPRIA positivity (p = 0.768) and BMPRII (p = 0.779). In the epithelial component of SA and UA, no statistically significant correlations between imunoexpression proteins analyzed were observed. In turn, the group of AOT, statistically significant positive correlations between the scores of expression of all studied proteins were found. In the stromal component, statistically significant positive correlations were found only in the SA group in BMP -4 and BMPRII (r = 0.476; p = .034), in the UA in BMP-4 and BMPRIA (r = 0.709; p = 0.022). The results of this study suggest that the BMPs and their receptors are involved in the development process odontogenic tumors. BMP-4, in turn, besides being present in odontogenic tumors have the capacity to form mineralized material.